Briskwalk inconjunction of Hari Sukan Negara 2024 (HSN 2024): team FPHP UITMCPP kita himpun! / Rabiatul Adawiyah Abd Rahman … [et al.] - Abd Rahman, Rabiatul Adawiyah; Mahat, Fadhlina; Ahmad, Johanna Adlin; Abd Hadi, Arnieyantie (Faculty of Hotel & Tourism Management, UiTM Pulau Pinang, 2025)
On 11th October 2024, UiTM Cawangan Pulau Pinang celebrated Hari Sukan Negara with a lively and well-attended briskwalk event, which saw students, faculty members, and administrative staff gathering to promote health, wellness, and community spirit. Team FPHP ensembles as the most number of teams together with other participants of all fitness levels, creating a vibrant scene as they walked the scenic route that highlighted the beautiful green spaces on campus.